Investigating halogens and MSA in the Southern Hemisphere: A spatial analysis - Segato, Delia (2024)
Sub-Antarctic islands and Antarctic coastal regions provide valuable sites for investigating environmental processes in the Southern Ocean. The fact that these sites are situated within the sea ice zone underscores their significance in investigating the impact of sea ice on the chemical composition of the boundary layer. In this study we report multi-year average levels of marine aerosols, including bromine, sodium, methanesulphonic acid and iodine, measured in five firn cores collected from sub-Antarctic Islands and coastal Antarctic sites. The records are compared with published Antarctic records to explore the spatial distribution of these species in the Antarctic region and their relationship with sea ice variability. Being mainly sourced from sea-salt aerosols, sodium and bromine exhibit the largest concentrations in the sub-Antarctic region, with progressively reduced deposition from the coast towards the central Antarctic plateau. Due to its gas-phase chemistry, bromine is depleted with respect to sodium in the sub-Antarctic sites. Bromine emitted in the form of sea-salt aerosols undergoes multi-phase recycling in the lower troposphere and, together with gas-phase bromine emitted from sea ice, is likely to be transported away from the source, depositing in enriched concentrations in the plateau compared to the Br/Na sea-water mass ratio. Similarly to bromine and sodium, methanesulphonic acid and iodine are found in higher concentrations in the sub-Antarctic sites, especially where the ocean is sea ice-covered during spring as primary production is stronger than in the ice-free ocean. Sea-salt mediated recycling of gas-phase iodine enhances its atmospheric lifetime, delivering enriched iodine depositions to the Antarctic plateau. Depicting the spatial distribution of these elements is of great importance for understanding the processes delivering these impurities around Antarctica.